Concurrent absorption and secretion of airway surface liquids and bicarbonate secretion in human bronchioles - Shamsuddin, A. K. M. (Am J Physiol Lung Cell Mol Physiol, 2019)
Although small airways account for the largest fraction of the total conducting airway surfaces, the epithelial fluid and electrolyte transport in small, native airway epithelia has not been well characterized. Investigations have been limited, no doubt, by the complex tissue architecture as well as by its inaccessibility, small dimensions, and lack of applicable assays, especially in human tissues. To better understand how the critically thin layer of airway surface liquid (ASL) is maintained, we applied a “capillary”-Ussing chamber (area ≈1 mm(2)) to measure ion transport properties of bronchioles with diameters of ~2 mm isolated from resected specimens of excised human lungs. We found that the small human airway, constitutively and concurrently, secretes and absorbs fluid as observed in porcine small airways (50). We found that the human bronchiolar epithelium is also highly anion selective and constitutively secretes bicarbonate ([Formula: see text]), which can be enhanced pharmacologically by cAMP as well as Ca(2+)-mediated agonists. Concurrent secretion and absorption of surface liquid along with [Formula: see text] secretion help explain how the delicate volume of the fluid lining the human small airway is physiologically buffered and maintained in a steady state that avoids desiccating or flooding the small airway with ASL.